1997
DOI: 10.1111/j.1468-2850.1997.tb00128.x
|View full text |Cite
|
Sign up to set email alerts
|

Detecting deception: Current models and directions.

Abstract: Traditional procedures for detecting deception are based on the global-signs-of-tying model, with its assumption that certain univenal, physiologically mediated signs result from attempts to deceive, independent of content. More recent attempts to detect deception can profitably be viewed from a cognitive rather than affective penpctive: (a) in terms of accuracy of knowledge, in which a person's success at deception regarding a paficular characteristic depends on the extent of his or her knowledge of that char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 42 publications
(56 reference statements)
0
17
0
Order By: Relevance
“…This provided a means of operationally defining malingering as MPQ, PDI, or MSPQ scores rarely produced by actual pain patients. This operational definition is consistent with Lanyon's (1997) accuracy of knowledge model of malingering, in which malingerers are identified by virtue of their lack of knowledge regarding the symptoms actual patients endorse. In Lanyon's model, one way malingering can be detected is by over-endorsing symptoms characteristic of a particular condition, because the malingerer lacks knowledge related to norms (i.e., how the typical patient would respond).…”
mentioning
confidence: 90%
“…This provided a means of operationally defining malingering as MPQ, PDI, or MSPQ scores rarely produced by actual pain patients. This operational definition is consistent with Lanyon's (1997) accuracy of knowledge model of malingering, in which malingerers are identified by virtue of their lack of knowledge regarding the symptoms actual patients endorse. In Lanyon's model, one way malingering can be detected is by over-endorsing symptoms characteristic of a particular condition, because the malingerer lacks knowledge related to norms (i.e., how the typical patient would respond).…”
mentioning
confidence: 90%
“…These findings bring into question whether all forms of malingering should be subsumed under the same overarching construct of malingering. Lanyon (1997), for instance, observed that reliance on a global signs of deception model is not supported by the empirical literature. Instead, different types of feigning occur in compensation-seeking circumstances, including the dissimulation of psychiatric, neuropsychological, and health problems (Larrabee, 2003).…”
mentioning
confidence: 93%
“…The idea that misrepresentation can be expressed in terms of simple dimensions (lying vs. not lying; faking good vs. faking bad) has now given way to the recognition that misrepresentation is better viewed as a multidimensional domain. Indeed, it is logical to assume that the particular patterns or ways in which respondents misrepresent themselves also vary across assessment areas such as clinical, vocational, forensic, and personnel (Lanyon, 1997). However, most of the relevant research has been done in the context of psychopathology, particularly with the Minnesota Multiphasic Personality Inventory (MMPI; Hathaway & McKinley, 1943) and MMPI-2 (Butcher, Dahlstrom, Graham, Tellegen, & Kaemmer, 1989).…”
mentioning
confidence: 98%